Finite-temperature regularization - Fosco, C. D. (2002)
We present a non-perturbative regularization scheme for Quantum Field Theories which amounts to an embedding of the original unregularized theory into a spacetime with an extra compactified dimension of length L ∼ Λ-1 (with Λ the ultraviolet cutoff), plus a doubling in the number of fields, which satisfy different periodicity conditions and have opposite Grassmann parity. The resulting regularized action may be interpreted, for the fermionic case, as corresponding to a finite-temperature theory with a supersymmetry, which is broken because of the boundary conditions. We test our proposal both in a perturbative calculation (the vacuum polarization graph for a D-dimensional fermionic theory) and in a non-perturbative one (the chiral anomaly).